PENGARUH FAKTOR SOSIAL EKONOMI DAN MANAJERIAL PETANI TERHADAP KEBERHASILAN USAHATANI MODEL AGROFORESTRI (Suatu Kasus Petani di Sekitar Hutan Daerah Borogojol, Kabupaten Majalengka, Jawa Barat) - Dasipah, Euis; Hermanto, Deden; Sukmawati, Dety; Suryani, Herni (Wanamukti: Jurnal Penelitian Kehutanan, 2024)
The objective of this investigation is to investigate the impact of Farmers' socio-economic and managerial factors on the success of agricultural enterprises using the agroforestry model. The respondent determination technique was implemented through a census of 65 respondents. Path analysis was implemented as the analytical methodology. The performance of the socio-economic factors of producers who were active in the Agroforestry model in the Borogojol forest area, which included age, education, experience, family responsibilities, land area, and capital, achieved an achievement criterion of 48.78%. Adequate. This demonstrates the socio-economic factors of farmers, as evidenced by their age (54 years), low education level (primarily elementary school graduates), family responsibilities (two individuals), limited land (0.26 hectares), and low capital. The hypothesis has been demonstrated that the agroforestry model is positively influenced by the socio-economic and managerial factors of producers, both simultaneously and partially. The total influence of the two variables is 67.00%, with 9.32% of the total influence being contributed by socio-economic factors and 57.69% by farmer managerial factors. The remaining 37.00% is influenced by other factors. To ensure that farmers remain engaged and continue to implement agroforestry farming models, it is necessary to increase the productivity of cultivated seasonal plant species by increasing the quantity of organic fertilizer used and providing coaching for follow-up and control. Keywords: Agroforestry, Economic, Social